The Effect of Polysaccharides Peptides Ganoderma Lucidum to Aortic Foam Cell Count and Lipid Profile in Type 2 Diabetic Model Rattus Norvegicus Strain Wistar - Djanggan Sargowo; Titin Andri Wihastuti; Cathrine Theodora Sukotjo; Prasanti Mahesa Anjani; Olivia Handayani; Liemena Harold Adrian (The Indonesian Biomedical Journal, 2017)
BACKGROUND: Type 2 Diabetes Mellitus (DM) is one of dominant factors in cardiovascular deaths and induces endothelial dysfunction. A definite sign of endothelial dysfunction is foam cells formation derived from oxidized LDL. This study was conducted to determine effect of Polysaccharides Peptides (PsP) Ganoderma lucidum to foam cell counts and lipid profile in diabetic model rats with high-fat diet.METHODS: Treatment group was categorized to negative control, positive control, DM-50, DM-150, and DM-300. Type 2 DM induced by Streptozotocin. PsP is administered with predetermined doses on each treatment’s group (50, 150, and 300 mg/kgBW) for 12 weeks. Measurements of foam cell count were held after obtaining rat’s aorta. To assess lipid profile, blood sample was taken from the rat's heart. Data analyzed by One-way ANOVA and Post Hoc Tukey tests.RESULTS: The administration of Ganoderma lucidum PsP to diabetic model rats provided a significant difference in lowering foam cell (p=0.017; CI 95%). It also gave significant difference between levels of each lipid components (Total Cholesterol, Trygliceride, LDL and HDL) in at least two treatment groups (p=0.010; CI 95%). Based on Post Hoc Tukey tests, the relationship between administration of PsP and foam cell is significant (p=0.002).CONCLUSION: PsP has antioxidant and anti-inflammatory effect in type 2 DM model Rattus norvegicus strain wistar, which can inhibit atherosclerosis and endothelial damage process. Further studies are necessary to evaluate the benefits of PsP as an adjuvant therapy in management of diabetic dyslipidemia.KEYWORDS: PsP, Ganoderma lucidum, foam cell, lipid profile, DM